Enforcement of foreign investment arbitral awards in Nigeria : a case study of the oil and gas sector - OluSoyeju, Olufemi Olugbemiga (University of Pretoria, 2017)
The presence of foreign investment in a developing nation brings about economic growth and development. It increases productivity, creates more jobs, promotes the use of local goods, motivates policies and economic reforms, transfers technological know-how and skills, increases revenue for the government, among others. Nigeria has attracted quite a huge stock of foreign direct investment over the years, majorly in the oil and gas sector. Nigeria's economy is greatly dependent on the revenues generated in the oil and gas sector and the economy thrives on this sector. Disputes arise between foreign investors and government entities ? the Federal Inland Revenue Services, Nigerian National Petroleum Corporation, and also with other foreign investors in the sector. These disputes are settled mostly out of court because core legislations in this sector provide that arbitration shall be the settlement mechanism. Hence, disputes are expected to be settled in quick successions, free of unnecessary domestic court intervention, and hurdle-free in the enforcement of arbitral awards. However, the reverse is the case in practice. The core aim of this research is to identify these challenges by reviewing recent arbitration cases in the oil and gas sector and to examine the legislative and procedural loop holes giving rise to such challenges. To arrive at effective recommendations, the arbitration system of Mauritius was analysed and compared to what is obtainable in Nigeria. From the comparison, this study proffers recommendations that would practically enhance the enforcement proceedings of foreign investment arbitral awards in Nigeria's oil and gas sector and subsequently in other sectors.